Circulating immune complexes in patients with breast cancer. Issue 6081 (23rd July 1977) - Hoffken, K; Meredith, I D; Robins, R A; Baldwin, R W; Davies, C J; Blamey, R W
Abstract : In a retrospective study in women with breast cancer circulating immune complex levels were measured by radioimmunoprecipitation with 125I-Clq. Before operation all the patients showed plasma immune complex levels significantly higher than those in controls. Twelve months after mastectomy patients identified clinicopathologically as having a good prognosis had almost normal levels of immune complexes. By contrast, patients with detectable dissemination on diagnosis or those who died within 22 months after mastectomy had significantly raised plasma levels. The tumour-specific nature of the immune complexes detected remains to be shown and suggestions about the applicability of this test not only for prognosis but also for monitoring the course of malignant diseases need to be confirmed by further investigations.